Analysis of the Relationship between Gross Domestic Product, Gini Ratio, and Human Development Index in Indonesia from 2012 to 2022 - Nur Amthori, Nadhif Zaim; Deasy, Venna; Henri, Juan (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2025)
Equitable income distribution and sustainable economic growth are two main pillars in improving the quality of life for society. This study aims to analyze the relationship between Gross Domestic Product (GDP) and the Gini Ratio on the Human Development Index (HDI) in Indonesia during the period 2012-2022. GDP is used as an indicator of economic performance, while the Gini ratio is used to measure income inequality. This research uses a quantitative approach with multiple regression analysis methods using secondary data obtained. The secondary data used were obtained from the Central Statistics Agency (BPS) and other official publications. Classical assumption tests were conducted to ensure the validity of the regression model, which included normality tests, multicollinearity, autocorrelation, and heteroscedasticity. The research results show that the Gini ratio has a positive and significant effect on the HDI, indicating that a decrease in income inequality tends to improve the quality of human development. Conversely, GDP has a positive but insignificant effect on the HDI, suggesting that economic growth contributes to the improvement of the quality of life for the community.